2002
DOI: 10.1021/jo010867v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Thermal Gas-Phase Isomerizations and Fragmentations of cis- and trans-1-(E)-Propenyl-2-methylcyclobutanes at 275 °C

Abstract: Kinetic studies of the thermal isomerization and fragmentation reactions exhibited by cis- and trans-1-(E)-propenyl-2-methylcyclobutanes at 275 degrees C in the gas phase have provided first-order rate constants for cis,trans interconversions of the cyclobutanes, 1,3-carbon migrations leading to 3,4- and 3,6-dimethylcyclohexenes, isomerizations providing directly and indirectly four acyclic dienes, and fragmentations to ethylene, propene, and mixtures of pentadienes and hexadienes. Both cis and trans isomers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…[37,38]. The stepwise mechanism first proposed by Burwell in 1952 is therefore the prevailing and generally accepted mechanism [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…[37,38]. The stepwise mechanism first proposed by Burwell in 1952 is therefore the prevailing and generally accepted mechanism [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of [1,5] and [1,7] chlorine and hydrogen shifts was reported by Okajima and Imafuku. 42 The authors were intrigued by the room-temperature 1 H NMR spectrum of 1,7,7-trichlorocycloheptatriene, which shows only three signals, indicative of a rapid rearrangement reaction.…”
Section: [1n] Sigmatropic Rearrangementsmentioning
confidence: 75%
“…42 The authors were intrigued by the room-temperature 1 H NMR spectrum of 1,7,7-trichlorocycloheptatriene, which shows only three signals, indicative of a rapid rearrangement reaction. This reaction could occur either via a direct [1,7] chlorine migration or via two sequential [1,5] chlorine migrations. The B3LYP/6-311G** computational study revealed that the concerted [1,7] suprafacial process, while formally forbidden, is lower energy than the [1,5] shift alternative.…”
Section: [1n] Sigmatropic Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DIBAL‐H reduction of 17 , followed by oxidation and addition of MeLi furnished the corresponding secondary alcohol, which was oxidatively transformed into the ketone 7 . The carboxylic acid 5 , the final component needed in the convergent approach, was prepared from 4‐penten‐1‐ol by a PCC oxidation,18 Wittig olefination, and hydrolysis sequence.…”
Section: Methodsmentioning
confidence: 99%